2016
DOI: 10.1177/107327481602300202
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Prognosis in Uveal Melanoma

Abstract: Assay validation, quality control, and interpretation of results are essential for the reliability and reproducibility of these tests. Although these prognostic tests have improved the ability to identify patients at increased risk for developing metastasis, their use has not changed the management of uveal melanoma. However, genomic, analytical, and sequencing technologies will provide a critical step toward useful targeted therapies for patients with high-risk uveal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…This supports the above‐mentioned findings of Barnhill et al in uveal melanoma, where angiotropism was found to be predictive of distant metastasis . Uveal melanoma typically metastasizes hematogenously, often to the liver, and the sclera lacks lymphatic channels. In our study, the association between angiotropism and distant metastasis was not significant in multivariate analysis ( P = 0.14).…”
Section: Discussionsupporting
confidence: 90%
“…This supports the above‐mentioned findings of Barnhill et al in uveal melanoma, where angiotropism was found to be predictive of distant metastasis . Uveal melanoma typically metastasizes hematogenously, often to the liver, and the sclera lacks lymphatic channels. In our study, the association between angiotropism and distant metastasis was not significant in multivariate analysis ( P = 0.14).…”
Section: Discussionsupporting
confidence: 90%
“…Tumor heterogeneity may possibly account for the discordant test results [1,22,23,24,25]. Each biopsy sample was obtained by an independent needle pass.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular prognostic biopsy for metastatic risk in the management of patients with uveal melanoma is standard of care at most major ophthalmic oncology practices in North America [1,2,3,4,5,6,7,8]. The loss of 1 copy of chromosome 3 (monosomy 3 [M3]) in the tumor tissue has been determined to be the risk factor most strongly associated with metastatic death originally reported in mostly large uveal melanoma [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…8q gain is a poor prognosis factor (more frequently associated with metastases) [51], mainly when it occurs in the context of 8p loss, suggesting the formation of an isochromosome 8q [13]. This frequently occurs in tumors that have lost a copy of chromosome 3, and it is considered an independent prognostic factor of progressive disease [52]. Gain of chromosome 8 or obtainment of an isochromosome 8q may be a posterior occurrence in the setting of uveal melanoma, and is verified in both low-and high-risk uveal melanomas [53].…”
Section: Molecular Pathology Of Uveal Melanomamentioning
confidence: 99%
“…Taking into account gene expression profile (15-gene expression panel), uveal melanomas can be divided into two distinct prognostic classes, namely class 1 tumors (which generally have the clinical and pathological features known to be associated with decreased metastatic risk, such as the presence of spindle cells), and class 2 tumors (which generally have more aggressive clinical and pathological features, with a higher risk for metastases). This test is commercially available for routine use in clinical practice [13,52].…”
Section: Risk Factors Detection and Diagnosis Of Uveal Melanomamentioning
confidence: 99%